Association between the administration of iron during pregnancy and the size of the child at birth in the Peruvian population - Guevara-Tirado, Alberto (2024)
Objective. To evaluate the association between having received iron during pregnancy and the size of the child at birth in the Peruvian population. Materials and methods. Descriptive, retrospective and cross-sectional study based on information obtained from the database of the National Institute of Statistics and Informatics (INEI), referring to the demographic and family health survey (ENDES) of the year 2021, which included a two-stage sample, probabilistic, stratified and independent, designed to be nationally representative. The variables considered were whether or not the patient received any iron supplement during pregnancy and the size of the child at birth. For the association analysis, the Pearson Chi-square test was performed using the SPSS statistics 25 software. Results. 51.10% of pregnant women who took iron supplements had children with normal weight, 46.50% of pregnant women who never took iron supplements had children with normal weight. The mothers in whose pregnancy did not consume iron supplements had more newborns with small size (23.70%) and very small (4.40%) than in those who did take iron supplements (19.10% and 2.70%), finding these variables were significantly associated (p value of=0.000 at a significance level of p<0.05). Conclusion. The size of the newborn during delivery is related to iron consumption in women of the Peruvian population.